2022
DOI: 10.1002/adma.202108827
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Diffusion Induced Capacity Losses in Lithium‐Based Batteries

Abstract: Rechargeable lithium‐based batteries generally exhibit gradual capacity losses resulting in decreasing energy and power densities. For negative electrode materials, the capacity losses are largely attributed to the formation of a solid electrolyte interphase layer and volume expansion effects. For positive electrode materials, the capacity losses are, instead, mainly ascribed to structural changes and metal ion dissolution. This review focuses on another, so far largely unrecognized, type of capacity loss stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 139 publications
0
44
0
Order By: Relevance
“…Without enough time or driving force to fully extract lithium ions from the electrode, a portion of lithium ions will be trapped within electrodes, which will accumulate gradually in the following cycles and finally lead to capacity fade. [61] For example, Nyholm and co-workers monitored the capacity and accumulated capacity loss in nanosilicon electrodes. [62] ICP-AES confirmed that the lithium ions can be trapped within electrodes during cycling.…”
Section: Loss Of Active Lithium Ionmentioning
confidence: 99%
“…Without enough time or driving force to fully extract lithium ions from the electrode, a portion of lithium ions will be trapped within electrodes, which will accumulate gradually in the following cycles and finally lead to capacity fade. [61] For example, Nyholm and co-workers monitored the capacity and accumulated capacity loss in nanosilicon electrodes. [62] ICP-AES confirmed that the lithium ions can be trapped within electrodes during cycling.…”
Section: Loss Of Active Lithium Ionmentioning
confidence: 99%
“…3 The discrepancy between the theoretical and experimental values of LiCoO2 has been attributed to the incomplete deintercalation of Li from LiCoO2. 26 Although our dataset may encourage researchers to focus on materials with energy densities above those of current LIB technology, we also note that other characteristics can be important. These include ionic and electrical conductivity, chemical compatibility with an electrolyte, electrochemical stability, and material recyclability.…”
Section: Figurementioning
confidence: 99%
“…2,3 Moreover, the cathode material plays a decisive role in the performance of lithium-ion batteries. 4 Among the available cathode materials, the lithium-rich layered cathode material xLi 2 MnO 3 -(1− x)LiTMO 2 (where TM = Ni, Co, Mn, etc.) has the advantages of high discharge specific capacity, high operating voltage, low cost, and environmental friendliness, compared with the traditional lithium-ion battery cathode materials (lithium iron phosphate cathode material, lithium manganate cathode material, lithium cobaltate cathode material), and is considered to have high potential for application.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, people are actively developing devices that utilize renewable energy sources and their efficient energy conversion and storage, in which lithium-ion batteries are rapidly becoming the main form of chemical energy storage with the advantages of high specific energy, good cycling performance, and environmental friendliness. , Moreover, the cathode material plays a decisive role in the performance of lithium-ion batteries . Among the available cathode materials, the lithium-rich layered cathode material x Li 2 MnO 3 -(1– x )­LiTMO 2 (where TM = Ni, Co, Mn, etc.)…”
Section: Introductionmentioning
confidence: 99%